Possible role for interleukins as biomarkers for mortality and recurrence in oral cancer. Issue 2 (April 2015) - Arduino, Paolo G.; Menegatti, Elisa; Cappello, Nazario; Martina, Eugenio; Gardino, Nicolò; Tanteri, Carlotta; Cavallo, Franco; Scully, Crispian; Broccoletti, Roberto
Background: Salivary and serum levels of interleukin-6 (IL-6) and interleukin-8 (IL-8) have previously been studied in oral cancer with conflicting results. Methods: We designed a controlled study to assess the correlation between pretreatment salivary and serum levels of IL-6 and IL-8, and all-cause survival and cancer recurrence in oral cancer patients. Results: Fifty-two oral cancer patients and 52 healthy control cases were selected. In univariate analysis, salivary IL-6 and IL-8 seemed to be more expressed in cases (p<0.001 and p = 0.010, respectively). Multivariate analysis showed that higher pretreatment saliva IL-6 levels were significantly associated with better survival (hazard ratio [HR] = 8.62; 95% confidence interval [95% CI], 1.21-62.50; p = 0.031). Conclusions: To date, this is the largest prospective controlled study that has analyzed the pretreatment salivary and serum levels of IL-6 and IL-8 in oral cancer patients, suggesting salivary IL-6 as a possible prognostic biomarker. But further validation in a larger sample is still necessary.